ROLE OF ULTRASONOGRAPHY IN MUSCULOSKELETAL DISEASES - Haydar Gök,; Gülay Dinçer, (Archives of Rheumatology, 2002)
Ultrasonography has an important role in many fields of medicine and has been used in the diagnosis and follow-up of musculoskeletal diseases in the last decade. Thanks to development of high resolution USG transducers, imaging of superficial soft tissues like joint, tendon, muscle and ligaments has become possible. The Advantages of USG are relatively low price, noninvaziveness, applicability by a single physician and its radiation free feature. Clinical use of USG in the musculoskeletal diseases is emphasized in this manuscript.